Finnish parliamentary speeches dataset - Salla Simola; Jeremias Nieminen; Janne Tukiainen (Scientific Data)
Abstract In this Data Descriptor, we introduce a dataset on Finnish parliamentary speeches and the background characteristics of politicians who speak in the parliament. The database includes all parliamentary speeches in Finland from the beginning of the existence of the Finnish parliament (years 1907-2018). These data have been used in previous studies to analyze questions related to political polarization, effects of media on parliamentary speeches, and political representation. The long time period makes it possible to study how historical changes are reflected in parliamentary speeches.